Student Preparation for PGY1 Residency Training by US Colleges of Pharmacy: Survey of the Residency Program Director Perspective. Issue 2 (February 2017) - Mutz, Alyssa B.; Beyer, Jacob; Dickson, Whitney L.; Gutman, Irina; Yucebay, Filiz; Lepkowsky, Marcie; Chan, Juliana; Carter, Kristen; Shaffer, Christopher L.; Fuller, Patrick D.
Purpose: To evaluate current residents' level of preparation by US colleges of pharmacy for postgraduate year 1 (PGY1) residency training from the perspective of residency program directors (RPDs). Methods: RPDs were asked in an electronic survey questionnaire to rate PGY1 pharmacy residents' abilities in 4 domains: communication, clinical knowledge, interpersonal/time-management skills, and professionalism/leadership. Results: One hundred ninety-seven RPDs of the American Society of Health-System Pharmacists (ASHP)–accredited PGY1 programs completed the survey. The majority of RPDs strongly agreed or agreed that residents were prepared as students to effectively communicate both verbally and nonverbally, were able to appropriately respond to drug inquiries using drug resources and literature searches, and consistently displayed professionalism. Respondents were more likely to disagree or give a neutral response when asked about residents' understanding of biostatistics and their ability to provide enteral and parenteral nutritional support for patients. Conclusion: Overall, RPDs agreed that residents were prepared to perform the majority of the tasks of each of the 4 domains assessed in this survey relating to PGY1 training. RPDs may use the results of this survey to provide additional support for their residents in the areas in which residents lack adequate preparation, while colleges of pharmacy may focus on incorporating more time in their curriculum for certain areas to better prepare their students for residency training.